Surgical treatment of electrical burns by local flap plastic surgery - Crkvenjas, Z; Tymonová, J; Adámková, M; Kadlcík, M; Klosová, H; Zámecníková, I (Acta chirurgiae plasticae, 2005)
Electrical burns are a serious problem within burn medicine even though they are relatively uncommon. The size of the burn is small, but the wound is often deep, and frequently the patient has systemic complications as well. In the majority of patients with such injuries immediate surgical intervention is essential, consisting of escharotomy, fasciotomy, and debridement of the devitalized tissues, necrectomy of the burn area, and closure of the defect by a direct suture, a dermo-epidermal graft, or local flap. Our report consists of three case studies. The patients underwent local flap plastic surgery after a full thickness soft tissue loss. All three patients healed primarily and did not require further correction of flaps. Final functional and aesthetic results are very good if the local flap is used appropriately.
Keywords: transplantace kůže; Adolescent; chirurgické laloky; Middle Aged; lidé středního věku; Skin Transplantation; lidé; debridement; mužské pohlaví; popálení elektrickým proudem; Burns, Electric; Male; Surgical Flaps; Debridement; Craniocerebral Trauma; mladiství; kraniocerebrální traumata; Humans